(untitled) (Medical Forum Monthly, 2024)
Objective: Determine the association of hormonal imbalance and infertility and any other endocrine disorder in the causation of infertility among female patients. Study Design: Observational / descriptive study. Place and Duration of Study: This study was conducted at the Govt. Aziz Bhatti Hospital (NSMC) for one year 2014-2015. Materials and Methods: Female patients who presented with primary and secondary infertility among patients who were married and in the reproductive age group (15-49). The hormone profile was advised on the day-2 of the menstrual cycle especially F.S.H, L.H and prolactin. The patients who presented with amenorrhea were given hormones for withdrawal bleeding and then profile done and at random in irregular bleeding. Thyroid hormones were advised depending upon the history and positive symptomatology. The study was not funded. The duration of infertility was not considered. Results: Majority of the patients who presented with infertility were in the reproductive age group, 51.8% from 20 to 29 and 44.44% from 30 to 39. Majority of the patients had normal hormone profile (64.81%). About 11.11% presented with polycystic ovarian syndrome (P.C.O’s), the same numbers with premature ovarian failure and about 7.4% with disturbed thyroid profile. Hyper-prolactinemia was not found as an important cause of infertility in this study. Conclusion: Hormone profile is an important investigation in cases of infertility in addition to the history, examination and ultrasonography, especially in cases that are also having associated menstrual abnormalities. Polycystic ovarian syndrome and premature ovarian failure were important causes of infertility and to some extent disturbed thyroid functions among the study group.